ANALISIS HUBUNGAN SELF-EFFICACY DAN METAKOGNITIF TERHADAP HASIL BELAJAR SISWA SMA BERDASARKAN GENDER PADA KONSEP GENETIKA - Suherman, Dewi Purnamasari (2015)
This study investigated the effect of self-efficacy beliefs and metacognitive on academic performance among high school students based on gender on Genetics concept. The background of this research is the lower of awareness, motivation, and regulation level that effected by self-efficacy and metacognitive. The purpose of this research is to analyze the effects of self-efficacy beliefs and metacognitive on academic performance among high school students based on gender on Genetic concept. Descriptive method is constructed this study. A total of 60 students XII grader of high school are participated in the study. Data were collected by Self-efficacy and Metacognitive Questionnaire, Genetic Concept Test, and Final Questionnaire. Data were analyzed using inferential statistics, regression. Regression analysis indicated that self-efficacy and metacognitive was a strong predictor of academic performance. This case are showed by the value of regression, so that self-efficacy and metacognitive were inferred was a strong predictor of academic performance. The other finding on this research show that there is a relation between self-efficacy and metacognitive in learning, there is a relation between self-efficacy and high school students' academic performance on Genetics concept, there is a relation between metacognitive and high school students' academic performance on Genetics concept, also show that male students are outperforming female students on self-efficacy, metacognitive, and academic performance ---------- Rendahnya kesadaran, motivasi, dan regulasi diri pada siswa dalam pembelajaran merupakan salah satu masalah utama dalam dunia pendidikan. Hal ini dapat dipengaruhi oleh self-efficacy dan metakognitif. Penelitian ini bertujuan untuk menganalisis hubungan self-efficacy dan metakognitif terhadap hasil belajar siswa SMA berdasarkan gender pada konsep Genetika. Metode penelitian yang digunakan merupakan metode deskriptif. Sebanyak 60 siswa kelas XII SMA dilibatkan dalam penelitian ini. Pengumpulan data dilakukan melalui instrumen berupa Kuesioner Self-efficacy dan Metakognitif, Tes Konsep Genetika, dan Angket. Data dalam penelitian ini diuji dengan menggunakan uji regresi. Hasil penelitian menunjukkan bahwa terdapat hubungan antara self-efficacy dan metakognitif dalam pembelajaran siswa SMA pada konsep Genetika, selain itu juga terdapat hubungan antara masing-masing variabel (self-efficacy dan metakognitif) terhadap hasil belajar siswa SMA pada konsep Genetika, serta terdapat perbedaan tingkat self-efficacy dan metakognitif pada siswa laki-laki menunjukkan hasil yang lebih tinggi dibandingkan dengan siswa perempuan dalam pembelajaran konsep Genetika dan berpengaruh terhadap hasil belajar. Hasil penelitian memberikan kesimpulan bahwa terdapat hubungan yang kuat antara self-efficacy dan metakognitif terhadap hasil belajar siswa SMA pada konsep Genetika